1998
DOI: 10.1111/j.1445-2197.1998.tb02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery and Timing of Hospital Discharge After Primary Total Hip Arthroplasty

Abstract: Background: Early discharge programmes in hospitals are encouraged to increase financial efficiency and bed availability, but standards of clinical care must not be compromised. Criteria for safe hospital discharge must be established and objective data are needed to assess how rapidly patients can achieve these discharge criteria. Methods: A prospective study was performed on 65 patients (mean age = 71 years) scheduled for primary total hip arthroplasty (THA). The Modified Barthel Index (MBI) was measured pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 5 publications
3
33
0
Order By: Relevance
“…We found that LOS was associated with certain patient characteristics. Increasing age was found to correlate with increasing LOS, which is in accordance with other, comparable studies (Kim et al 1993, Wang et al 1998, Watkins et al 1999, Hayes et al 2000. Women had longer stays than men and patients living alone stayed longer, which has also been shown in most studies (Rissanen et al 1996, Liebergall et al 1999, Watkins et al 1999, Hayes et al 2000.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found that LOS was associated with certain patient characteristics. Increasing age was found to correlate with increasing LOS, which is in accordance with other, comparable studies (Kim et al 1993, Wang et al 1998, Watkins et al 1999, Hayes et al 2000. Women had longer stays than men and patients living alone stayed longer, which has also been shown in most studies (Rissanen et al 1996, Liebergall et al 1999, Watkins et al 1999, Hayes et al 2000.…”
Section: Discussionsupporting
confidence: 85%
“…There is no clear-cut explanation for this finding. Co-morbidities resulted in increased LOS-a finding shared by others (Wang et al 1998, Wasielewski et al 1998, Hayes et al 2000. Preoperative use of walking aids was associated with increased LOS.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some of the results that were only significant in the univariate analysis might be accounted for by different medical comorbidities of the patients, and the lack of the American Society of Anesthesiologists (ASA) grading for our cohort is a limitation of this study. Medical comorbidities clearly correlate with prolonged course of hospitalization [6,8,42], especially with the ASA scores of 3 and 4 [12]. Another limitation is the retrospective nature of the data, as well as the lack of reported outcome scores and operative times.…”
Section: )mentioning
confidence: 99%
“…Medical comorbidities clearly correlate with prolonged course of hospitalization [6,8,42], especially with the ASA scores of 3 and 4 [12]. In addition, univariate analysis involves measurement of one variable at a time, while multivariate analysis involves multiple variable and accounts for confounding effect.…”
Section: )mentioning
confidence: 99%